(untitled) (Perner’s Contacts, 2011)
The paper introduces a simulation model of hump shunting process which is modelled by two phases – first phase corresponds to the preparation of arriving trains for shunting and second phase to shunting over a hump. We distinguish two types of shunting – primary shunting of arriving trains which are considered to be customers and secondary shunting which we model as breakdowns of the system. The simulation model was created by using software CPN Tools which is intended for editing and simulating of coloured Petri nets. In the end of the paper simulation outcomes are compared with outcomes gained by solving of corresponding mathematical model which was presented in the previous issue.